Impact of Change Management : A Case Study of Select Indian Manufacturing Organizations - Gupta, Sanjiv (Prabandhan: Indian Journal of Management, 2018)
The last two decades saw brisk changes in consumer perception. Indian organizations competed with multinational companies and offered the best-quality products at most competitive prices as and when required by the customer. After the liberalization of the Indian economy, the Indian organizations, which were earlier operating in a protective market, faced tough competition not only for exporting their products, but also to find a market within the country. These conditions necessitated the adoption of a change process by the Indian industry. Most organizations adopted the ’change management’ methodology to compete and grow their businesses nationally and internationally. Through change management, every level of an organization can be accessed and transformed. The strategies include transformation of systems both within and outside the organization - production process, quality process, inventory process, and sales and marketing. This paper studied the change management methodology adopted by four leading manufacturing organizations and the results achieved by them in various business parameters. They were bestowed with various quality awards in the last decade. The study was conducted from July to December 2017.